Audio-Visual Resources in the Social Studies Department of President Ramon Magsaysay State University - Roneil S. Aramay; Irish E. Flores (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This quantitative descriptive study sought to establish the perceived competency and benefits of audio-visual resources (AVRs) among 60 President Ramon Magsaysay State University Social Studies teachers in Academic Year 2023-2024. The demographic profiles of the teachers, their use of AVRs, and the perceived effects on teaching efficiency, creativity, improvisation, and expressiveness were investigated. Data analysis indicated that the respondents were predominantly female, in middle adulthood, having a Master's degree, at the instructor rank, and with relatively new tenure. The findings indicated that the Social Studies instructors strongly agree that AVRs significantly enhance their teaching ability, creativity, improvisation, and expressiveness. Moreover, they demonstrated great confidence in their ability to select, prepare, and utilize AVRs correctly. Perceived benefits of AVRs were significantly influenced by academic rank and length of service but not by sex, age, or educational attainment. Conversely, perceived competence in AVR use was significantly influenced by sex, educational attainment, and academic rank but not by age or length of service. Recommendations to university administrators are to evaluate infrastructure for AVR capability, and to Social Studies teachers, perform AVR comparative studies and investigate the effect of self-assessed competence on student achievement. Future studies could examine the effects of demographic factors on AVR usage and perceived advantage and seek to find targeted areas of support to improve teaching efficiency.